How to implement market models using VBA - Goossens, Francois, 1960- (Chicester, West Sussex UK : John Wiley & Sons, Inc., 2015)
"Accessible VBA coding for complex financial modellingImplementing Market Models Using VBA makes solving complex valuation issues accessible to any financial professional with a taste for mathematics. With a focus on the clarity of code, this practical introductory guide includes chapters on VBA fundamentals and essential mathematical techniques, helping readers master the numerical methods to build an algorithm that can be used in a wide range of pricing problems. Coverage includes general algorithms, vanilla instruments, multi-asset instruments, yield curve models, interest rate exotics, and more, guiding readers thoroughly through pricing in the capital markets area. The companion website features additional VBA code and algorithmic techniques, and the interactive blog provides a forum for discussion of code with programmers and financial engineers, giving readers insight into the different applications and customisations possible for even more advanced problem solving. Financial engineers implement models from a mathematical representation of an asset's performance by building a program that performs a valuation of securities based on this asset. Implementing Market Models Using VBA makes this technical process understandable, with well-explained algorithms, VBA code, and accessible theoretical explanations. Decide which numerical method to use in which scenario Identify the necessary building blocks of an algorithm Write clear, functional VBA code for a variety of problems Apply algorithms to different instruments and models Designed for finance professionals, this book brings more accurate modelling within reach for anyone with interest in the market. For clearer code, patient explanation, and practical instruction, Implementing Market Models Using VBA is an essential introductory guide"--
6.2.1 Generic Heath-Jarrow-Morton6.2.2 LMM (LIBOR market model); Chapter 7 Stochastic Volatilities; 7.1 The Heston model; 7.1.1 Code; 7.1.2 A faster algorithm; 7.1.3 Calibration; 7.2 Barrier options; 7.2.1 Numerical results; 7.2.2 Code; 7.3 Asian-style options; 7.4 SABR model; 7.4.1 Caplets; 7.4.2 Code; Chapter 8 Interest Rate Exotics; 8.1 CMS swaps; 8.1.1 Code; 8.2 Cancelable swaps; 8.2.1 Code; 8.2.2 Tree approximation; 8.3 Target redemption note; 8.3.1 Code; Bibliography; Index; EULA.
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Finance -- Mathematical models -- Computer programs; Visual Basic for Applications (Computer program language); BUSINESS & ECONOMICS -- Finance; Finance -- Mathematical models -- Computer programs; Visual Basic for Applications (Computer program language); Electronic books